Qualitative Circulation Space Application at the ‘Tunjungan Plaza’ Shopping Mall in Surabaya - Sriti Mayang Sari (IJCAS (International Journal of Creative and Arts Studies), 2014)
Public circulation space is an interior element that organizes and connects the different parts of a shopping mall together. As such the circulation space is partly defined by the different accommodation of shops, anchor stores, catering and leisure facilities. In considering the organizational framework to be established by the public circulation space the objectives can be separately identified into functional and qualitative requirements. The functional requirements are essential primary planning considerations and the qualitative requirements are recommended secondary planning and more detailed design considerations. The goal of this research is to identify the qualitative circulation requirements at Tunjungan Plaza, Surabaya, as one of the biggest shopping mall in East Java. As a result of the field identification will create some recommendations for the qualitative circulation requirement that suitable for the shopping mall visitor.